2011
DOI: 10.1111/j.1939-1668.2011.01060.x
|View full text |Cite
|
Sign up to set email alerts
|

Gay until Proven Straight: Exploring Perceptions of Male Interior Designers from Male Practitioner and Student Perspectives

Abstract: Given the small percentage of men studying interior design versus the higher percentage of men in the profession, and misperceptions of male designers among the general public, there is a need to examine sexual identity and stereotyping in the interior design industry. While researchers have explored the experiences of gay men working ''straight jobs'' and men doing ''women's work'' (e.g., nursing, teaching), very little research to date has focused on the experience of men (gay and straight) in careers that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…Our findings from Study 5 demonstrated that belief in gaydar perpetuates the use of stereotypes to jump to conclusions about orientation. Left unchecked, these stereotypes can lead to a host of adverse consequences (e.g., Cox & Devine, 2014; Matthews & Hill, 2011; Nadal, 2013). For example, as has recently been demonstrated (Cox & Devine, 2014), using a stereotypic cue to privately infer group membership can free prejudice perpetrators from concerns about social condemnation for their prejudice, yielding higher levels of prejudice-based aggression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings from Study 5 demonstrated that belief in gaydar perpetuates the use of stereotypes to jump to conclusions about orientation. Left unchecked, these stereotypes can lead to a host of adverse consequences (e.g., Cox & Devine, 2014; Matthews & Hill, 2011; Nadal, 2013). For example, as has recently been demonstrated (Cox & Devine, 2014), using a stereotypic cue to privately infer group membership can free prejudice perpetrators from concerns about social condemnation for their prejudice, yielding higher levels of prejudice-based aggression.…”
Section: Discussionmentioning
confidence: 99%
“…This function is readily apparent in the media, which has a history of using stereotypic cues to imply that a character is gay or lesbian (Cartei & Reby, 2012; Dennis, 2009; Russo, 1987). Indeed, an abundance of self-report, correlational, and experimental evidence has shown that people rely on stereotypic attributes, such as fashion, hairstyle, or femininity/masculinity, to make judgments about orientation (self-report: Matthews & Hill, 2011; Shelp, 2002; correlational: Ambady, Hallahan, & Conner, 1999; Freeman, Johnson, Ambady, & Rule, 2010, Studies 2 & 3; Gaudio, 1994; Johnson, Gill, Reichman, & Tassinary, 2007, Study 3; Rieger et al, 2010; Smyth, Jacobs, & Rogers, 2003; Van Borsel, & Van de Putte, 2014; experimental: Cox & Devine, 2014; Dotsch et al, 2011, Study 3; Freeman et al, 2010, Study 1; Johnson et al, 2007, Studies 1 & 2).…”
Section: Inferences About Sexual Orientation: the Role Of Stereotypesmentioning
confidence: 99%
“…Also, based on past work and our own theorizing, stereotypes related to these two groups seem especially likely to reveal heterogeneous directionality. Because the defining features of gay male group membership (i.e., same-sex attraction, gay identity) are not visible, people often rely on stereotypic cues (e.g., fashion) to infer that men are gay [ 27 28 , 50 51 ]. Gay male stereotypes, therefore, are often used in the negative, Attribute → Group direction, which suggests to us that they may be more likely to possess negative directionality.…”
Section: Studymentioning
confidence: 99%
“…While a small number of studies still considered gay men and lesbians in occupations stereotypically associated with those demographics, such as gay men in professional dance (Bailey & Oberschneider, 1997) or interior decorating (Matthews & Hill, 2011), or lesbians in the skilled trades (Weston & Rofel, 1984), most research efforts in the collective identity tradition examined more mainstream occupational pursuits.…”
Section: How Does Discrimination Against Sexual Minorities Operate Atmentioning
confidence: 99%